AUTOMATIC CONTROL OF A WHEELED ROBOT - Ratsimbalison Ralaitsitohaina Tafitasoa Carlos; Ratsimba Mamy Nirina; Ramafiarisona Hajasoa Malalatiana (International Journal of Innovations in Engineering Research and Technology, 2024)
This work aims to automatically control a wheeled robot from a specific location A to another B. We assume the robot’s trajectory is straight (the line (AB)). To solve this problem, we need the coordinates of point A and point B, i.e., the position sensor’s state. A microcontroller must then process this information. Next, the variation in coordinates mean displacement, and this variation depends on speed, so we also interest in speed here. Finally, for the robot to arrive at point B, its direction of movement must be the same as the direction of (AB). The direction depends on the orientation angle of the moving robot.